KESESUAIAN DAN DAYA DUKUNG LAHAN UNTUK KEGIATAN WISATA DAN PERIKANAN DI PANTAI KOTA MAKASSAR SULAWESI SELATAN - Hamzah, Hamzah; Fahrudin, Achmad; Efendi, Heffni; Muchsin, Ismudi (FAPETKAN UNTAD, 2011)
This research is intended 1) to know land suitability for tourism and fisheries at Makassar's coastal area 2) to calculate carryng capacity area for conducting tourism and fisheries at City coastal area of Makassar. This research done be conducted in City coastal area of Makassar South Sulawesi. Method used in research is land suitability analysis and carryng capacity coastal area for beach tourism and fisheries. Research result suitable area for beach tourism is 10.373,7 m. There Is even for Â diving tourism is as extensive as 4,3 ha at Samalona's Island waters. Land suitability for floating cages is 490, 39 ha, seaweeds culture area is 1000,4 h. Carryng capacity for floating cages 8,796 ha, while is 3.258 units available. By use of long line method, therefore acquired 231 units on area as extensive as 554,25 ha. Carryng capacity for beach tourism : kayangan island 15 person; Lae Lae 53 ; Tanjung Bayang, Tanjung Bunga and Akarena 162 person; Losari's beach 137 person; Barombong's beach is 47 person. Key words : City coastal, area of Makassar South.